Patient and public involvement in primary care research - an example of ensuring its sustainability. Issue 1 (December 2015) - Jinks, Clare; Carter, Pam; Rhodes, Carol; Taylor, Robert; Beech, Roger; Dziedzic, Krysia; Blackburn, Steven; Hughes, Rhian; Ong, Bie
Abstract Background The international literature on patient and public involvement (PPI) in research covers a wide range of issues, including active lay involvement throughout the research cycle; roles that patients/public can play; assessing impact of PPI and recommendations for good PPI practice. One area of investigation that is less developed is the sustainability and impact of PPI beyond involvement in time-limited research projects. Methods This paper focuses on the issues of sustainability, the importance of institutional leadership and the creation of a robust infrastructure in order to achieve long-term and wide-ranging PPI in research strategy and programmes. Results We use the case of a Primary Care Research Centre to provide a historical account of the evolution of PPI in the Centre and identified a number of key conceptual issues regarding infrastructure, resource allocation, working methods, roles and relationships. Conclusions The paper concludes about the more general applicability of the Centre's model for the long-term sustainability of PPI in research.